Highly active ozonides selected against drug resistant malaria - Lobo, Lis (2018)
Ever increasing multi-drug resistance by Plasmodium falciparum is creating new challenges in malaria chemotherapy. In the absence of licensed vaccines, treatment and prevention of malaria is heavily dependent on drugs. Potency, range of activity, safety, low cost and ease of administration are crucial issues in the design and formulation of antimalarials. We have tested three synthetic ozonides NAC89, LC50 and LCD67 in vitro and in vivo against multidrug resistant Plasmodium. In vitro, LC50 was at least 10 times more efficient inhibiting P. falciparum multidrug resistant Dd2 strain than chloroquine and mefloquine and as efficient as artemisinin (ART), artesunate and dihydroartemisinin. All three ozonides showed high efficacy in clearing parasitaemia in mice, caused by multi-drug resistant Plasmodium chabaudi strains, by subcutaneous administration, demonstrating high efficacy in vivo against ART and artesunate resistant parasites.